2004
DOI: 10.1007/s10875-004-6247-0
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 Cytokines and IgE Levels in Identical Twins with Varying Levels of Cigarette Consumption

Abstract: Some have suggested that tobacco smoke may skew the immune system toward a Th2 pattern, however the effects of genetics or childhood exposures could explain these results. We compared PMBC supernatant or serum Th1 (INF-gamma) and Th2 (IL-4, IL-5, and IL-13) cytokine and IgE levels in members of 45 pairs of nonasthmatic monozygotic twins with varying levels of current cigarette consumption to determine if smoking was associated with Th1/Th2 function after accounting for genetic factors. A statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…They determined significant dose responses between heavy smokers (>20 cigarettes/day) and light smokers (<20 cigarettes/day) in monocyte production of IL-5 (166% higher in heavy smokers) and IL-13 (146% higher in heavy smokers) but observed no significant differences in IL-4 production. 156 These cytokines are more consistent with an increased Th2 type immune response in heavier smokers, with consequences that would be in accord with greater susceptibility to intracellular pathogens, as Yin et al observed in response to heavy diesel exhaust particle exposure. 133 In the first part of this section, the inflammatory burst-producing cytokine type response was emphasized, whereas in the latter part, discussion emphasizing sensitization, immunological suppression and alternative activation of macrophages was discussed.…”
Section: Toxicological Consequences Of Metallo-particle Inhalation Spmentioning
confidence: 73%
“…They determined significant dose responses between heavy smokers (>20 cigarettes/day) and light smokers (<20 cigarettes/day) in monocyte production of IL-5 (166% higher in heavy smokers) and IL-13 (146% higher in heavy smokers) but observed no significant differences in IL-4 production. 156 These cytokines are more consistent with an increased Th2 type immune response in heavier smokers, with consequences that would be in accord with greater susceptibility to intracellular pathogens, as Yin et al observed in response to heavy diesel exhaust particle exposure. 133 In the first part of this section, the inflammatory burst-producing cytokine type response was emphasized, whereas in the latter part, discussion emphasizing sensitization, immunological suppression and alternative activation of macrophages was discussed.…”
Section: Toxicological Consequences Of Metallo-particle Inhalation Spmentioning
confidence: 73%
“…The only significant determinant of smoking persistence was having a co-twin who continued to smoke. In a second study, we were the first to demonstrate that smoking was directly associated with increased interleukin-5 and interleukin-13 levels (Cozen et al, 2004a).…”
Section: Smokingmentioning
confidence: 92%
“…38,39 Previous reports of an association between HL and smoking have usually been strongest in EBV-positive HL [40][41][42][43] ; we did not have enough information on EBV tumor status to evaluate this relationship. Although adult-onset eczema is a common clinical manifestation of HL, 44 the majority of twins with a history of eczema reported an onset in early childhood, and the remainder at least 5 years before diagnosis, so reverse causality is not a likely explanation of the association.…”
Section: Protective Role For Early Oral Exposures In Yahlmentioning
confidence: 98%